2021
DOI: 10.3389/fphar.2021.702032
|View full text |Cite
|
Sign up to set email alerts
|

Leismanicidal Activity of Propolis Collected in the Semiarid Region of Brazil

Abstract: Objective: The aim of the current study is to investigate the chemical composition, cytotoxic effect, and leishmanicidal activity of propolis collected in the semi-arid region of Bahia, Brazil.Methods: EtOH extract, hexane, EtOAc and MeOH fractions from propolis were analyzed by ultra-performance liquid chromatography coupled with diode array detector and quadrupole time-of-flight mass spectrometry. The identification was based on the exact mass, general fragmentation behaviors and UV absorption of the flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Recently, compounds isolated from Brazilian propolis have demonstrated activity in vitro against Leishmania greater than that shown by the accepted treatment [ 8 ]. The bioavailability of propolis in humans is not well established, although there have been some limited studies of temperate propolis where the flavonoids, which are abundant in this type of propolis, appear to be well absorbed but are extensively metabolised [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, compounds isolated from Brazilian propolis have demonstrated activity in vitro against Leishmania greater than that shown by the accepted treatment [ 8 ]. The bioavailability of propolis in humans is not well established, although there have been some limited studies of temperate propolis where the flavonoids, which are abundant in this type of propolis, appear to be well absorbed but are extensively metabolised [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since propolis contains a multitude of chemical components in a complex mixture, its biological activity and pharmacological properties might similarly be broad [ 1 , 2 ]. Propolis has been observed to have promising activity against a number of protozoal species, particularly Trypanosoma and Leishmania species [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Studies of the antiprotozoal activity of propolis have recently been reviewed [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herbalists have recommended propolis according to its antibacterial, antiviral and anti-inflammatory activity, which can be used in the treatment of different types of infections as well as duodenal and gastric ulcers [ 1 , 8 ]. Many biological activities of propolis have been confirmed by modern studies, including anticancer [ 9 ], antioxidant [ 10 ], antileishmanial [ 11 ], wound healing [ 12 ], anti-inflammatory [ 13 ] and immunomodulatory [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the leishmanicidal effect of different extracts of propolis both in vitro and in vivo ( Devequi-Nunes et al, 2018 ; Regueira-Neto et al, 2018 ; Cavalcante et al, 2021 ). Previously, our group described the leishmanicidal and immunomodulatory effects of three different extracts of green propolis in Leishmania braziliensis infection in vitro, as well as directly on the promastigote forms of this parasite ( Rebouças-Silva et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%